PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP HASIL BELAJAR SENI RUPA DI SMA N 1 2X11 KAYU TANAM KABUPATEN PADANG PARIAMAN - MITA DESILVA, Drs. Syafril R. M.Pd, Drs. Wisdiarman, M.Pd (Serupa The Journal of Art Education, 2014)
ning outcomes of students in the learning Arts Arts in SMA N 1 2x11 WoodPlant Padang Pariaman . The hypothesis tested in this study is the result of the teaching and learning of Fine Arts students are taught with the use of media images ( experimental class ) differ significantly with learning outcomes Arts students are taught without the use of media images ( grade control ) . The population in this study were all students who take Arts subjects . The sample is majoring in social studies class XI students who take Arts subjects . Engineering pengampilan sample is purposive sampling . This type of research is a quasiexperiment ( Quasi Experiment ) with a pretest - posttest study design Control Group Design . Data were collected by achievement test . Data were analyzed by t test .The findings in this study indicate that : student learning outcomes by using media images better , when compared with students who are taught without the use of media images . Based on the above research findings , it can be concluded that the use of media images influence on student learning outcomes in Arts subjects . Therefore the use of media images in learning is needed by every educator to improve student learning outcomes , especially in subjects Culture ArtKata kunci : Pengaruh, Media Gambar, Hasil Belajar,Seni Rupa